Systemic therapy with or without transcatheter intra-arterial therapies for unresectable hepatocellular carcinoma: a real-world, multi-center study - Pan, Yangxun; Zhu, Xiaodong; Liu, Jianwei; Zhong, Jianhong; Zhang, Wei; Shen, Shunli; Jin, Renan; Liu, Hongzhi; Ye, Feng; Hu, Kuan; Xu, Da; Zhang, Yu; et al. (Frontiers in Immunology, 2023)
Background. Systemic therapy is recommended as standard therapy in treating hepatocellular carcinoma (HCC) patients who were diagnosed with advanced HCC and is suggested for unresectable HCC (uHCC). Transcatheter intraarterial therapies (TRIT) was widely applied to uHCC patients in Chinese practice. Methods. This study aimed to investigate the survival benefit of concurrent TRIT and systemic therapy as first-line treatment for patients with uHCC. This real-world, multi-center retrospective study was conducted in consecutive patients who were treated at 11 centers in China since September 2018 to April 2022. Patients in the combination group received systemic therapy together with TRIT, and the systemic group included those received only systemic therapy. Results. Of the 289 uHCC patients who were eligible for this study, 146 patients were classified to the combination group, and 143 belong to the systemic group. The median OS was significantly longer in the combination group than systemic group (not reached vs. 23.9 months; hazard ratio [HR], 0.561; 95% confidence interval [CI], 0.366 to 0.861; P=0.008) before, after propensity score matching (HR, 0.612; 95% CI, 0.390 to 0.958; P=0.031) and inverse probability of treatment weighting adjusted (HR, 0.539; 95% CI, 0.116 to 0.961; P=0.008). The subgroup analysis revealed the potential advantage patients for concurrent TRIT included those with liver tumors beyond “up-to-seven” criteria, absence of extrahepatic metastasis, and AFP ≥400 ng/mL. Conclusion. Concurrent TRIT with systemic therapy as first-line treatment associated with better survival in uHCC patients, especially for those with intensive intrahepatic tumor load and no extrahepatic metastasis.